Perilaku Modern Adultery Warga Jemaat Dewasa GMIM Moria Wulurmaatus: Tinjauan Etika Seksual-Pedagogis - Maria Mema; Iky Sumarthina P. Prayitno (Integritas: Jurnal Teologi, 2022)
This paper focuses on the study of social and pedagogical ethics related to modern sexual behavior, adultery for adult congregations and the teaching of sexual ethics education for adult congregations by GMIM Moria Wulurmaatus. Sex is basically good, holy, and as a gift that has been given by God. As human beings who have been created, the noblest must have the right sexual ethics, so that sex is integrated within the scope of holy marriage. Based on the phenomenon that occurred in the congregation, adult members of the congregation who have a role and ensure the existence of the church have engaged in sexual behavior outside of marriage. To examine the sexual behavior of adult congregations and GMIM Moria Christian sexual education. Data collection was carried out using qualitative research methods with data collection techniques using observation and interview techniques. Sexual behavior of adult members of the congregation has become a modern style today, this is due to the lack of discussing and celebrating sex in marriage. It is through this that GMIM Moria Wulurmaatus realizes that it is the church that has the responsibility to provide education for the members of the congregation, because the church is capable of basing responsibility on the only right reason related to sex